Preliminary Memorandum on IV Five Year Plan of the Union Territory of Laccadive, Minicoy and Amindivi Islands - Planning Commission (Planning Commission, 1965)
This Union Territory consists of twenty Islands and three sand banks scattered in the Arabian Sea. Out of these ten are inhabited by a population of 24,108. For centuries these people were completely neglected. Even after Independence it was apparently not possible Tor the Madras State to go into the detailed necessities of these isolated people. It was only after the States’ Reorganization that these Islands were formed into a Union territory and the 'people were classified as Scheduled Tribes. Thus it was only on 1-11-1956 that an integrated approach was made for the development of this area. During the period 1956-58 not much progress could be achieved as the time was spent in investigation and preparation for the developmental activities.
The Union Territory of Laccadive, Minicoy and Amindivi Islands
Government of India Planning Commission
Keywords: General Introduction; Agriculture; Animal Husbandry; Fisheries; Co-Operation; Transport and Communications; Miscellaneous Schemes; Size And Pattern Of Investment; Financial Resources of the Plan; District and Block Plans And City Plans; Machinery for Planning